Between hope and reality: how oncology physicians and information providers of a cancer information service manage patients' expectations for and experiences with immunotherapies - Ihrig, Andreas; Richter, Jenniffer; Bugaj, Till Johannes; Friederich, Hans-Christoph; Maatouk, Imad (Patient education and counseling, 2023)
Objectives - Immune checkpoint inhibitors have established themselves as a further therapeutic pillar in the treatment of various types of cancer. This can create challenges and possible misunderstandings for patients. The aim of this study was to assess the experiences of physicians and information providers in their interactions with patients about immunotherapy. - Methods - The study design was exploratory with qualitative research methodology. We performed focus groups with 8 oncology physicians and 9 information providers of a cancer information service. - Results - In the coding process, five focal points could be identified: (1) image of immunotherapy, (2) presentation of immunotherapy in the media, (3) hope, (4) creation of an information base, and (5) lessons learned and future directions. Physicians and information providers report that immunotherapy has a very positive image among patients. This seems to be due to the presentation of immunotherapy in the media and the positive associations of people with terms such as the immune system and the body's own defense. - Conclusions - In contrast to chemotherapy, patients are at risk of underestimating the early symptoms of serious side effects of immunotherapy. From the point of view of physicians, the exaggerated expectations of patients regarding the possibilities of immunotherapy are often not met. The challenge for practitioners is to consider patients' expectations to provide balanced information and recommendations. - Practical implications - Communication skills training and up-to-date information tools should improve physician-patient communication.